Expression and diagnostic relevance of heat shock protein 90 and signal transducer and activator of transcription 3 in malignant pheochromocytoma. Issue 4 (15th January 2013) - Xu, Yunze; Qi, Yicheng; Rui, Wenbin; Zhu, Yu; Zhang, Chongyu; Zhao, Juping; Wei, Qing; Wu, Yuxuan; Shen, Zhoujun; Ning, Guang
Abstract : Background: Malignant pheochromocytoma (PCC) is a rare catecholamine producing tumour with a poor prognosis. For many years predicting PCC behaviour has remained a highly difficult task. The aim of this study was to evaluate heat shock protein 90 (HSP90) and signal transducer and activator of transcription 3 (STAT3) as tissue-based markers to predict malignant PCC. Methods: Ninety-two sporadic PCC patients were enrolled. We compared the expression of HSP90 and STAT3 by immunohistochemistry of benign versus malignant PCCs. In addition, in 17 snap frozen PCC and in 7 healthy adrenal tissues, we investigated the expression of HSP90 and STAT3 by means of western immunoblot. Results: Positive staining for HSP90 was observed in 22.37% (95% CI 13.00% to 31.74%) of the benign and 66.67% (95% CI 44.89% to 88.45%) of the malignant cases. Similarly, STAT3 staining was seen in 26.32% (95% CI 16.42% to 36.22%) of the benign versus 83.33% (95% CI 66.11% to 100.55%) of the malignant cases. Using HSP90 and STAT3 combined, the positive predictive value of malignancy was signiﬁcantly increased to 0.70 (95% CI 0.45 to 0.86). Besides, logistic regression analysis showed that HSP90 (OR=3.667, p=0.039) and STAT3 (OR=9.474, p=0.002) were independently associated with malignant PCC. Conclusions: This study has conﬁrmed that malignant PCC overexpress HSP90 and STAT3, and the combination of HSP90 and STAT3 can be used as helpful diagnostic markers to distinguish malignant from benign PCCs.